Examining the continuous usage intention and behaviours of music streaming subscribers. (8th February 2022) - Yeoh, Shih Yee; Yuntavid, Xavier J.P.; Chin, Phaik Nie
Live music streaming trends will go to the next level with an enhanced 5G technology and networks. In this study, we examined determinants on consumers' continuous usage intention and their actual usage behaviours towards music streaming services using the C-TAM-TPB. Price value and legal concern were added as an extended TPB as well as moderating effect of age. A total of 235 usable data was collected through an online self-administered questionnaire across the country. We used the partial least squares structural equation modelling (PLS-SEM) for analysis of the measurement model and the structural model. The findings reveal that perceived usefulness and perceived ease of use positively affect consumers' attitude towards music streaming. Attitude towards music streaming, subjective norms and price value are key determinants of consumers' continuous usage intention. Consumers' continuous usage intention affects their behaviours towards music streaming services.